Os testemunhos na cobertura ao vivo do incêndio da boate Kiss - Oliveira, Juliana Motta de (2016)
The research deals with the participation of witnesses in live news coverage of Kiss Nightclub fire. The tragedy occurred in the city of Santa Maria (RS), on January 27, 2013, caused the death of 242 youths and had worldwide repercussions. The coverage has exposed not only drama of the survivors and families of the victims, but the complexity of journalistic work in an unstructured environment where productive routines are disrupted and hampered access to official sources. From this context enhanced by the immediacy of live coverage, there is the rise of eyewitness sources. As the theoretical part, three perspectives are presented: the constructionist theories, with the understanding journalism as a speech due to a number of conditions and configurative circumstances of the produced content, and governed by a communications contract; the theories of journalism, with the understanding of the central role of sources in the construction of journalistic discourse; and studies of the testimony, with the concept of presumed reliability, truth-effect and reality marking of such testimony. Based on these assumptions, understanding the roles played by the testimonies in coverage and discuss how the constitutive thrill of a disaster situation is aimed, transformed into pathos effect from the manifestation of the testimonies, contributes not only to the target capture, as well as for information. For this, live the entries broadcast by Globo Television Network and its RBS TV affiliate, on January 27, 28 and 29, 2013 are analyzed, from the systematization of Patrick Charaudeau on the discursive means to prove the truth ( designation, reconstruction and elucidation) and to give emotion (pathos effect). On the eyewitnesses manifestation there was a predominance of real evidence (66.7%). However, it is suggested that given the context of the tragic event, the pathos effect is present even in the statements of the target information. Likewise, it is observed that the sequences classified as pathos effect also present informational content. Thus, it is concluded that the communication contract gained new dimensions in disaster situations, making the feeling making gets closer to knowledge making.